Can Eu Anomaly Indicate a Hydrothermal Fluid Si Source? A Case Study of Chert Nodules From the Permian Maokou and Wujiaping Formations, South China - Li, Chenqing; Cui, Yixin; Ning, Meng; Li, Chao; Xing, Chaochao; Xia, Pan; Dong, Lin (Frontiers in Earth Science, 2022)
The Middle-Late Permian witnessed an unusual chert accumulation event along the margin of the Pangea and Paleo-Tethys realms, known as ‘Permian Chert Event (PCE)’. The PCE is well recognized in the Permian limestone from South China, in the forms of nodular and bedded cherts. Previous studies suggested that PCE was caused by hydrothermal fluid related to the Emeishan Large Igneous Province (ELIP). Meanwhile, another hypothesis supported biogenic origin of PCE, i.e., the Permian chert derived from biosilicification of abundant sponges and radiolarian. Thus, sources of silica from the Permian chert remain uncertain. To understand linkages among PCE, biosilicification mechanism and the ELIP event, this study focused on chert nodules collected from the Permian Maokou and Wujiaping formations in Lianziya and Maoertang sections, South China. We measured germanium/silicon ratios (Ge/Si) and Rare Earth Element (REE) compositions of chert nodules on the basis of petrographic analysis. Ge/Si ratios range from 0.14 to 0.63 μmol/mol with an average of 0.33 μmol/mol (n=18) in Lianziya section and from 0.02 to 0.75 μmol/mol with an average of 0.18 μmol/mol (n=45) in Maoertang section, both of which are close to the seawater value. The REE pattern is characterized by LREE-depleted with positive Eu anomaly ranging from 0.66 to 2.16 in Lianziya section and from 1.05 to 9.57 in Maoertang section. Our results indicate that the silica of the Permian chert predominantly originated from seawater with limited contributions from hydrothermal fluids. To further quantify the contributions of hydrothermal fluids, we applied a binary (seawater and hydrothermal fluid) mixing model based on two geochemical proxies, i.e., Ge/Si ratio and Eu anomaly. The modeling results suggest a mixing of 0.5 vol.% to 1 vol.% hydrothermal fluids with contemporaneous seawater, verifying dominant seawater source of silica in the PCE. Although it has been widely accepted that positive Eu anomaly points to hydrothermal fluid origin of silica, our study demonstrates that positive Eu anomaly could also present in cherts that predominantly derive from normal seawater. Therefore, the analysis of Ge/Si ratio or REE compositions are highly recommended when determining the Si source of cherts.